Duration of antiretroviral therapy among people living with HIV and incidence of hypertension in Ghana. Issue 12 (30th October 2020) - Sarfo, Fred Stephen; Singh, Arti; Tagge, Raelle; Mensah, Gideon; Ovbiagele, Bruce
Abstract: Understanding the differential rates of incident hypertension among People Living with HIV (PLWH) based of duration of exposure to combination antiretroviral therapy (cART) may provide insights into the pathogenesis of hypertension in this population. Utilizing the dataset of a prospective study conducted at a Ghanaian tertiary medical center, we evaluated factors associated with incident hypertension among PLWH previously naïve to cART before study enrollment (cART newly prescribed group, n = 221) versus PLWH established on cART for at least a year (cART established group, n = 212). New‐onset hypertension was diagnosed as clinic BP > 140/90 mmHg on two separate clinic visits over 12‐month follow‐up. Cox proportional hazards regression models were used to assess factors associated with incident hypertension. Mean age of new versus cART established was 41.1 ± 8.2 versus 45.1 ± 8.6 years ( p < .001), with more women in the cART established group (68.3 vs. 82%, p = .0009). There were 105 (24.3%) episodes of incident hypertension over 328 person‐years follow‐up (PYFU), incidence rate of 320.1 (95% CI: 263.1‐385.9)/1000 PYFU, with higher rates in new versus cART established (476.6/1000 PYFU vs. 222.8/1000 PYFU, p = 0.0002). Overall, age by increasing decile (aHR 0.76; 95% CI: 0.59‐0.98), log HIV‐1 viral load (aHR 1.16; 1.04‐1.35), and use of tenofovir (aHR 1.66; 1.04‐2.64) were associated with incident hypertension. While CD4 counts, age, BMI, pre‐diabetes, and urban/peri‐urban residency were independently associated with hypertension in the cART established group; no independent predictors were identified among the cART newly prescribed group. Further studies to explore the potential mechanisms underlying incidence of hypertension in PLWH are warranted.